2019
DOI: 10.5937/vojtehg67-18446
|View full text |Cite
|
Sign up to set email alerts
|

Decision making model in forest road network management

Abstract: Forest resource exploitation and the achievement of full forest potential depend on the density and quality of the forest road network. The forest road network has to fulfill multiple functions; it thus has strategic importance in forest management. When planning the forest road network development, decision makers have to consider various technological, economic, social, and environmental factors. A comprehensive and functional approach is needed. A hybrid methodological framework for the formulation of guide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The LBWA model is used for expressing real relations among criteria, without approximations of the expert judgments. Moreover, the LBWA model eliminates deviations of expert judgments that appear after using scales with a small range of values [37]. By eliminating this kind of problem, we also eliminate the approximation of expert judgments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The LBWA model is used for expressing real relations among criteria, without approximations of the expert judgments. Moreover, the LBWA model eliminates deviations of expert judgments that appear after using scales with a small range of values [37]. By eliminating this kind of problem, we also eliminate the approximation of expert judgments.…”
Section: Discussionmentioning
confidence: 99%
“…We emphasize this because when increasing the level of consistency in the AHP and the BWM, expert judgments are distorted as a result of the violation of the consistency of the model. The mentioned problem is often due to the use of the nine-point scale, which has limited possibilities for expressing expert judgments [37]. The LBWA model has the following advantages: (1) enables rationally expressing the judgments of a decision-maker with a minimal number of comparisons, n − 1; (2) eliminates the shortcomings of nine-point that are described in many studies (Asadabadi et al, 2019); and (3) the shown model has great flexibility while expressing expert judgments and it eliminates discrepancies which can occur with models that use the pairwise comparison technique.…”
Section: The Lbwa Model For Determining Weighted Coefficient Of the Criteriamentioning
confidence: 99%
“…Fuzzy logic techniques are efficient in solving complex, ill-defined problems that are characterized by uncertainty of environment and fuzziness of information [36,37]. Taking into account that disturbances and noises are common sources of uncertainties, it can be concluded that from the aspect of fuzzy implementation this system is highly resistant to noise and disturbance [38,39,40]. The fuzzy membership functions for the input linguistic variables, as well as the output linguistic variable are given in Figure 6.…”
Section: Fuzzy Inference Systemmentioning
confidence: 99%